High LIN28A Expressing Ovarian Cancer Cells Secrete Exosomes That Induce Invasion and Migration in HEK293 Cells. (25th October 2015) - Enriquez, Vanessa A.; Cleys, Ellane R.; Da Silveira, Juliano C.; Spillman, Monique A.; Winger, Quinton A.; Bouma, Gerrit J.
Abstract : Epithelial ovarian cancer is the most aggressive and deadly form of ovarian cancer and is the most lethal gynecological malignancy worldwide; therefore, efforts to elucidate the molecular factors that lead to epithelial ovarian cancer are essential to better understand this disease. Recent studies reveal that tumor cells release cell-secreted vesicles called exosomes and these exosomes can transfer RNAs and miRNAs to distant sites, leading to cell transformation and tumor development. The RNA-binding protein LIN28 is a known marker of stem cells and when expressed in cancer, it is associated with poor tumor outcome. We hypothesized that high LIN28 expressing ovarian cancer cells secrete exosomes that can be taken up by nontumor cells and cause changes in gene expression and cell behavior associated with tumor development. IGROV1 cells were found to contain high LIN28A and secrete exosomes that were taken up by HEK293 cells. Moreover, exposure to these IGROV1 secreted exosomes led to significant increases in genes involved in Epithelial-to-Mesenchymal Transition (EMT), induced HEK293 cell invasion and migration. These changes were not observed with exosomes secreted by OV420 cells, which contain no detectable amounts of LIN28A or LIN28B. No evidence was found of LIN28A transfer from IGROV1 exosomes to HEK293 cells.